2014
DOI: 10.14486/ijscs46
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Perfectionism and Burnout in Junior-Elite Athletes

Abstract: The purpose of the present investigation was to examine the relationship between multidimensional perfectionism and athlete burnout. The target population of research consisted of 168 elite handball players who participate in National Junior Championships. 123 athletes were selected randomly as the sample. We used a multi-section inventory to collect data, contained measures of multidimensional perfectionism, dispositional achievement goals, athlete burnout, perceived satisfaction with goal attainment and perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…The ESAs had a strong personal motivation to strive for perfection. This could be a prominent determinant in their dual career development (Aghdasi, 2014). The ESAs' character also included commitment, dedication, being hardworking and driven, versatility, and ability (Miller, Homan, & Miniutti, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The ESAs had a strong personal motivation to strive for perfection. This could be a prominent determinant in their dual career development (Aghdasi, 2014). The ESAs' character also included commitment, dedication, being hardworking and driven, versatility, and ability (Miller, Homan, & Miniutti, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Acerca de la asociación negativa baja entre perfeccionismo y realización personal, se evidencia, cuando los sanitarios necesitan realizar un trabajo perfecto, sin margen de error, pensamiento desmotivador, que puede conducir a la frustración, decepción e insatisfacción. Lo que confirman, Aghdasi (2014); Balevre et al (2012), en relación a la dimensión de baja realización personal, antagónico con el agotamiento emocional y desperzonalización.…”
Section: Discussionunclassified
“…Hill (2011) [32] (Team) 202 male rugby players aged 16-24 in the UK Correlation (r) MPS-H [5] ABQ [17] Article Hill (2010) [33] (Team) 150 male and female canoe/kayak athletes aged 13-55 in the UK Correlation (r) MPS [5] ABQ [17] Article Aghdasi (2014) [24] (Team) 123 male and female youth handball players in Turkey Correlation (r) MPS [5] ABQ [17] Article…”
Section: Type Of Publicationmentioning
confidence: 99%
“…These scales show conflicting results for the sub-factors. For example, Ho et al [23] and Aghdasi [24], who used the MPS and ABQ, found negative results in the relationship between SOP and burnout; conversely, positive results were found in the relationship between SPP and burnout. Regarding OOP, which is the third factor of the MPS, Olsson et al [25] and Park [26] found a positive relationship between OOP and burnout, whereas Zhang [27] and Kim et al [28] found negative relationships, indicating that the results vary greatly among studies.…”
Section: Introduction 1research Purpose and Significancementioning
confidence: 99%